Case report: Secondary failure to tolvaptan in a patient with SCLC and paraneoplastic SIADH - Menzi, Sheryl; Jaramillo, Silvia Daniela; Pfister, Stephan; Schefer, Hubert; Jehle, Andreas Werner (Frontiers in Endocrinology, 2024)
The syndrome of inappropriate antidiuretic hormonesis secretion (SIADH) is frequent in lung cancer patients. Here, we report a case with persistent hyponatremia, which suggested malignant SIADH and facilitated an early diagnosis of small cell lung cancer (SCLC). A combined radio-chemotherapy led to a partial remission and resolution of SIADH. An early relapse was indicated by reoccurring severe hyponatremia and increased copeptin levels, which were used as surrogate markers for the antidiuretic hormone (ADH). As palliative immunochemotherapy, together with fluid restriction and solute substitution, were unable to control hyponatremia, treatment with the ADH V2-receptor antagonist tolvaptan was initiated. Over time, the dose of tolvaptan needed to be increased, paralleled by a well-documented exponential increase of copeptin levels. In summary and conclusion, this is a rare case of a secondary failure to tolvaptan with unique documentary evidence of increasing copeptin levels. This observation supports the hypothesis that exceedingly high ADH levels may lead to competitive displacement of tolvaptan from the V2 receptor.